Analisis Proses Bisnis Pada Sistem Automatisasi Persuratan Mahasiswa Uin Sunan Kalijaga - Anifah Putri Utami; Arawinda Khairunnisa; Ridhayani Ridhayani; Sumarsono Sumarsono (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2024)
As a student, it is often necessary to make various kinds of letters for different kinds of needs, such as letters of good behavior, letters of application for permits, certificates of still studying, letters of receiving scholarships and so on. For the sake of convenience and productivity in working by utilizing advanced information technology, UIN Sunan Kalijaga has created a mailing automation information system for students which is a website designed to make it easier for students to make letters for lecture purposes. The activity in making the UIN Sunan Kalijaga letter automation information system is a business process with a series of several business activities that are interrelated with one goal so that business targets are achieved. Therefore, a business process must be planned and designed as well as possible in order to minimize errors that might occur. Business process analysis is an attempt to study a business process in one or several organizations. The purpose of the business process analysis is to analyze and document existing work processes. The automation information system of UIN Sunan Kalijaga uses a development model with the waterfall method which is one of the best solutions because it utilizes information technology as an intermediary to simplify and speed up human work. The results of this study are in the form of system modeling which is presented in Use Case Diagrams, Activity Diagrams, Entity Relationship Diagrams and System Displays used in the information system of letter automation at UIN Sunan Kalijaga.